Expression of Lysyl Oxidase Predictive of Distant Metastasis of Laryngeal Cancer. (24th January 2017) - Lee, Yoon Se; Park, Yangsoon; Kwon, Minsu; Roh, Jong‐Lyel; Choi, Seung‐Ho; Nam, Soon Yuhl; Kim, Sang Yoon
Abstract : Objective: To investigate the prognostic significance of lysyl oxidase (LOX) expression in laryngeal cancer. Study Design: Retrospective chart review and histologic analysis. Setting: Tertiary referral academic center. Subjects and Methods: Patients (N = 100) underwent surgical treatment for laryngeal cancer and had tissue specimens available. Immunohistochemical staining for LOX was performed on laryngeal cancer tissue microarrays, and the proportion and intensity of staining were evaluated. Patients with LOX scores ≤6 were classified into the low LOX group, while those with scores >6 were classified into the high LOX group. We analyzed the correlation between LOX expression and clinical factors as well as prognosis. Results: LOX was predominantly expressed in the cytoplasm and nuclei of tumor cells. Kaplan‐Meier analysis revealed that the high LOX group had worse overall survival and recurrence‐free survival rates than the low LOX group ( P <. 05). LOX expression exhibited marginally significant correlation with lymph node metastasis. In the Cox regression analysis, LOX expression and lymph node metastasis were significant factors correlated with overall survival rate (odds ratio [OR] = 3.92, 95% confidence interval [95% CI]: 1.35‐11.37, P =. 012; OR = 1.96, 95% CI: 0.93‐1.43, P =. 024, respectively). LOX expression was related to distant metastasis free survival rate (OR = 7.72, 95% CI: 1.02‐19.18, P =. 048). Conclusion: A high expression level of LOX is associated with lymph node and distant metastasis as well as poor prognosis among patients with laryngeal cancer.